Efficacy, non-target impacts, and costs of mechanical control options against a bioturbator in bivalve aquaculture - Jennifer L. Ruesink; C. Haleh Mawson; Brian Allen; Jeffrey Barrett; David Beugli; Steven Booth; Laura Butler; Bill Dewey; Cinde R. Donoghue; Brett R. Dumbauld; Kristine Feldman; Zachary Forster; et al. (Aquaculture, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Data driven food fraud vulnerability assessment using Bayesian Network: Spices supply chain - Y. Bouzembrak; N. Liu; W. Mu; A. Gavai; L. Manning; F. Butler; H.J.P. Marvin (Food Control, 2024)

The value of adding black carbon to community monitoring of particulate matter - Rebecca A. Sugrue; Chelsea V. Preble; James D.A. Butler; Alaia J. Redon-Gabel; Pietro Marconi; Karan D. Shetty; Lee Ann L. Hill; Audrey M. Amezcua-Smith; Boris R. Lukanov; Thomas W. Kirchstetter (Atmospheric Environment, 2024)

Blood chemistry and biliverdin differ according to reproduction and tourism in a free-living lizard - Susannah S. French; Erin L. Lewis; Kwanho C. Ki; Zachary E. Cullen; Alison C. Webb; Charles R. Knapp; John B. Iverson; Michael W. Butler (Journal of Comparative Physiology B, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Contrasting Futures for Australia’s Fisheries Stocks Under IPCC RCP8.5 Emissions – A Multi-Ecosystem Model Approach - Heidi R. Pethybridge; Elizabeth A. Fulton; Alistair J. Hobday; Julia Blanchard; Catherine M. Bulman; Ian R. Butler; William W. L. Cheung; Leo X. C. Dutra; Rebecca Gorton; Trevor Hutton; Richard Matear; Hector Lozano-Montes; et al. (Frontiers in Marine Science, 2020)

Advances in Mechanistic Approaches to Quantifying Biophysical Fire Effects - J. J. O’Brien; J. K. Hiers; J. M. Varner; C. M. Hoffman; M. B. Dickinson; S. T. Michaletz; E. L. Loudermilk; B. W. Butler (Current Forestry Reports, 2018)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Trends in marine climate change research in the Nordic region since the first IPCC report - M. W. Pedersen; A. Kokkalis; H. Bardarson; S. Bonanomi; W. J. Boonstra; W. E. Butler; F. K. Diekert; N. Fouzai; M. Holma; R. E. Holt; K. Ø. Kvile; E. Nieminen; et al. (Climatic Change, 2016)

Integrating Top-Down and Bottom-Up Adaptation Planning to Build Adaptive Capacity: A Structured Learning Approach - J. R. A. Butler; R. M. Wise; T. D. Skewes; E. L. Bohensky; N. Peterson; W. Suadnya; Y. Yanuartati; T. Handayani; P. Habibi; K. Puspadi; N. Bou; D. Vaghelo; et al. (Coastal Management, 2015)

Displacement Forecasting Method in Brittle Crack Surrounding Rock Under Excavation Unloading Incorporating Opening Deformation - X. J. Li; W. M. Yang; L. G. Wang; I. B. Butler (Rock Mechanics and Rock Engineering, 2014)

Yeast copper–zinc superoxide dismutase can be activated in the absence of its copper chaperone - Kevin W. Sea; Yuewei Sheng; Herman L. Lelie; Lindsay Kane Barnese; Armando Durazo; Joan Selverstone Valentine; Edith Butler Gralla (JBIC Journal of Biological Inorganic Chemistry, 2013)

Nest box design for the study of diurnal raptors and owls is still an overlooked point in ecological, evolutionary and conservation studies: a review - Marcel M. Lambrechts; Karen L. Wiebe; Peter Sunde; Tapio Solonen; Fabrizio Sergio; Alexandre Roulin; Anders Pape Møller; Bernat C. López; Juan A. Fargallo; Klaus-Michael Exo; Giacomo Dell’Omo; David Costantini; et al. (Journal of Ornithology, 2012)

Gold Nanoparticle Penetration and Reduced Metabolism in Human Skin by Toluene - Hagar I. Labouta; David C. Liu; Lynlee L. Lin; Margaret K. Butler; Jeffrey E. Grice; Anthony P. Raphael; Tobias Kraus; Labiba K. El-Khordagui; H. Peter Soyer; Michael S. Roberts; Marc Schneider; Tarl W. Prow (Pharmaceutical Research, 2011)

Time-Correlated Single Photon Counting For Simultaneous Monitoring Of Zinc Oxide Nanoparticles And NAD(P)H In Intact And Barrier-Disrupted Volunteer Skin - Lynlee L. Lin; Jeffrey E. Grice; Margaret K. Butler; Andrei V. Zvyagin; Wolfgang Becker; Thomas A. Robertson; H. Peter Soyer; Michael S. Roberts; Tarl W. Prow (Pharmaceutical Research, 2011)

The efficacy of detecting variants with small effects on the Affymetrix 6.0 platform using pooled DNA - Charleston W. K. Chiang; Zofia K. Z. Gajdos; Joshua M. Korn; Johannah L. Butler; Rachel Hackett; Candace Guiducci; Thutrang T. Nguyen; Rainford Wilks; Terrence Forrester; Katherine D. Henderson; Loic Le Marchand; Brian E. Henderson; et al. (Human Genetics, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Broad‐scale latitudinal patterns of genetic diversity among native European and introduced house sparrow ( Passer domesticus ) populations - A. W. SCHREY; M. GRISPO; M. AWAD; M. B. COOK; E. D. McCOY; H. R. MUSHINSKY; T. ALBAYRAK; S. BENSCH; T. BURKE; L. K. BUTLER; R. DOR; H. B. FOKIDIS; et al. (Molecular Ecology, 2011)
Introduced species offer unique opportunities to study evolution in new environments, and some provide opportunities for understanding the mechanisms underlying macroecological patterns. We sought to determine how introduction history impacted genetic diversity and differentiation of the house sparrow ( Passer domesticus ), one of the most broadly distributed bird species. We screened eight microsatellite loci in 316 individuals from 16 locations in the native and introduced ranges. Significant population structure occurred between native than introduced house sparrows. Introduced house sparrows were distinguished into one North American group and a highly differentiated Kenyan group. Genetic differentiation estimates identified a high magnitude of differentiation between Kenya and all other populations, but demonstrated that European and North American samples were differentiated too. Our results support previous claims that introduced North American populations likely had few source populations, and indicate house sparrows established populations after introduction. Genetic diversity also differed among native, introduced North American, and Kenyan populations with Kenyan birds being least diverse. In some cases, house sparrow populations appeared to maintain or recover genetic diversity relatively rapidly after range expansion (

Activation amplitude patterns do not change for back muscles but are altered for abdominal muscles between dominant and non-dominant hands during one-handed lifts - Heather L. Butler; Cheryl L. Hubley-Kozey; John W. Kozey (European Journal of Applied Physiology, 2009)

Visual cortex activation in kinesthetic guidance of reaching - W. G. Darling; R. J. Seitz; S. Peltier; L. Tellmann; A. J. Butler (Experimental Brain Research, 2007)

Photochemical reactivity of siderophores produced by marine heterotrophic bacteria and cyanobacteria based on characteristic Fe(III) binding groups - Katherine Barbeau; Eden L. Rue; Charles G. Trick; Kenneth W. Bruland; Alison Butler (Limnology and Oceanography, 2003)
Siderophores, high‐affinity Fe(III) ligands produced by microorganisms to facilitate iron acquisition, might contribute significantly to dissolved Fe(III) complexation in ocean surface waters. In previous work, we demonstrated the photoreactivity of the ferric ion complexes of several α‐hydroxy carboxylic acid—containing siderophores produced by heterotrophic marine bacteria. Here, we expand on our earlier studies and detail the photoreactivity of additional siderophores produced by both heterotrophic marine bacteria and marine cyanobacteria, making comparisons to synthetic and terrestrial siderophores that lack the α‐hydroxy carboxylate group. Our results suggest that, in addition to secondary photochemical reaction pathways involving reactive oxygen species, direct photolysis of Fe(III)‐siderophore complexes might be a significant source of Fe(II) and reactive Fe(III) in ocean surface waters. Our findings further indicate that the photoreactivity of siderophores is primarily determined by the chemical structure of the Fe(III) binding groups that they possess—hydroxamate, catecholate, or α‐hydroxy carboxylate moieties. Hydroxamate groups are photochemically resistant regardless of Fe(III) complexation. Catecholates, in contrast, are susceptible to photooxidation in the uncomplexed form but stabilized against photooxidation when ferrated. α‐Hydroxy carboxylate groups are stable as the uncomplexed acid, but when coordinated to Fe(III), these moieties undergo light‐induced ligand oxidation and reduction of Fe(III) to Fe(II). These photochemical properties appear to determine the reactivity and fate of Fe(III)‐binding siderophores in ocean surface waters, which in turn might significantly influence the biogeochemical cycling of iron.

Relationship Between Six Years of Corn Yields and Terrain Attributes - Thomas C. Kaspar; Thomas S. Colvin; Daniel B. Jaynes; Douglas L. Karlen; David E. James; David W. Meek; Daniel Pulido; Howard Butler (Precision Agriculture, 2003)

Condensed tannins in Leucaena and their relation to psyllid resistance - R. A. Wheeler; W. R. Chaney; L. G. Butler; J. L. Brewbaker (Agroforestry Systems, 1994)

The kinetics of methylmercury administered repeatedly to rats - L. Magos; W. H. Butler (Archives of Toxicology, 1976)

Study of the phenolic compounds in potato tubers during storage - C. C. Craft; H. W. Siegelman; W. L. Butler (American Journal of Potato Research, 1958)

s of papers presented at the Forty-First annual meeting - R. E. Anderson; A. P. Benson; W. J. Hooker; Gerard S. Birth; Karl H. Norris; Reiner Bonde; Robert Akeley; Donald Merriam; C. C. Craft; H. W. Siegelman; W. L. Butler; L. A. Dionne; et al. (American Journal of Potato Research, 1958)

Sectional notes - H. W. Poulsen; H. G. Zuckerman; C. H. Metzger; W. B. Ward; W. C. Edmundson; E. R. Bennet; R. A. Jehle; A. B. Beaumont; John S. Gardner; E. L. Newdick; Frank W. Hussey; E. J. Wheeler; et al. (American Journal of Potato Research, 1934)

Preliminary seed certification notes - E. R. Dykeman; C. H. Hadley; W. A. McCubbin; Harold L. Bailey; O Butler; M. F. Barrus; R. F. Payne; N. W. Glimes; H. O. Werner; W. Stuart; Donald Folsom; W. H. M. (American Journal of Potato Research, 1923)